PENGARUH PERBANDINGAN LIDAH BUAYA (Aloe barbadensis Miller) DAN TERONG BELANDA (Solanum betaceum Cav.) TERHADAP KARAKTERISTIK MINUMAN SERBUK INSTAN - Sirait, Ira Monicha; Timur Ina, Putu; Indri Hapsari, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 4 No 1 (2015): Jurnal ITEPA, 2015)
This study aims to determine 1) the comparison effect of aloe vera and tamarillo to the characteristics of the instant powder drinks, 2) the best characteristics of aloe vera and tamarillo ratio. This study used a Randomized Block Design with 6 treatments of the aloevera and tamarillo ratio: 100% : 0%; 95% : 5%; 90% : 10%; 85% : 15%; 80% : 20% and 75% : 25% . The treatment was repeated 3 times to obtain 18 experimental units, if there was a significant difference (P<0,05) of the treatment it will be followed by Duncan Multiple Range Test. The results showed that the ratio of aloevera and tamarillo = 75% : 25% has the best water content (1,45% wb), vitamin C (7,03% wb), total sucrose (46,23% wb), antioxidant activity (53,17% wb), the time of rehydration (28,33 seconds), color, aroma, flavor  and overall acceptance is rather like.
Keywords: Aloe vera (Aloe barbadensis Miller), tamarillo (Solanum betaceum Cav.), instant powder drink